An Investigatory Project of Squash (Cucurbita pepo) as an Alternative Facial Cream Mask: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Pumpkin’s brightening and anti-ageing benefits can be enjoyed by most skin types. Additionally, the B vitamins in pumpkin make it a great acne treatment. Being versatile, those with dry skin types can enjoy pumpkin's brightening benefits by using it with other hydrating ingredients. The research design was quantitative-experimental research. This study's statistical treatment was a t-test used to determine the difference between the two groups of respondents. The researchers used a questionnaire to determine the level of acceptability of the Alternative Facial Cream Mask in terms of construction materials, procedures and design, effectivity, and presentation.  The study's respondents are 5 STEM Teachers and 5 Selected STEM Students. The following procedures were undertaken in the process of developing the Alternative Facial cream mask: The following procedures were undertaken in the process of developing the alternative facial cream mask: prepare the materials, slice the squash into pieces, stew the sliced squash, put the stewed sliced squash into a bowl, crush the squash and add two teaspoons of honey, put one teaspoon of olive oil in the mixture, mix using a fork or spoon until it softens. This will be put in a jar and presented to the project. The study results in construction materials, procedures and design, and presentation. Overall, the STEM Teachers interpreted it as highly acceptable. While the STEM students’ is interpreted as very highly acceptable. The t-computed value is 0.401, and the t-critical value is 1.108. Therefore, there is no significant difference between the assessments of the two groups. To further improve the project, the respondents recommended adding antioxidant ingredients to help the product last long and other ingredients like egg white to tighten and firm the skin. For the packaging, use vacuum-sealed or air-tight containers for longer product storage. To give a quality impression, make the appearance presentable and pleasing to the eyes.
Keywords: Squash; Facial cream mask